11.3k views
3 votes
Drag the tiles to the boxes to form correct pairs.

Match each operation involving Rx) and g(x) to its answer.
(t) = 1 - 22 and g(x) = V11 — 41

1 Answer

4 votes

Answer:


(g + f)(2) = \sqrt 3 - 3


((f)/(g))(-1) = 0


(g + f)(-1) = √(15)


(g * f)(2) = -3\sqrt 3

Explanation:

Given


f(x) =1 - x^2


g(x) = \sqrt{11 - 4x

See attachment

Solving (a): (g + f)(2)

This is calculated as:


(g + f)(2) = g(2) + f(2)

Calculate g(2) and f(2)


g(2) \to √(11 - 4 * 2) = √(3)


f(2) = 1 - 2^2 = -3

So:


(g + f)(2) = g(2) + f(2)


(g + f)(2) = \sqrt 3 - 3

Solving (b):
((f)/(g))(-1)

This is calculated as:


((f)/(g))(-1) = (f(-1))/(g(-1))

Calculate f(-1) and g(-1)


f(-1) = 1 - (-1)^2 = 0

So:


((f)/(g))(-1) = (f(-1))/(g(-1))


((f)/(g))(-1) = (0)/(g(-1))


((f)/(g))(-1) = 0

Solving (c): (g - f)(-1)

This is calculated as:


(g + f)(-1) = g(-1) - f(-1)

Calculate g(-1) and f(-1)


g(-1) = √(11 - 4 * -1) = √(15)


f(-1) = 1 - (-1)^2 = 0

So:


(g + f)(-1) = g(-1) - f(-1)


(g + f)(-1) = √(15) - 0


(g + f)(-1) = √(15)

Solving (d): (g * f)(2)

This is calculated as:


(g * f)(2) = g(2) * f(2)

Calculate g(2) and f(2)


g(2) \to √(11 - 4 * 2) = √(3)


f(2) = 1 - 2^2 = -3

So:


(g * f)(2) = g(2) * f(2)


(g * f)(2) = \sqrt 3 * -3


(g * f)(2) = -3\sqrt 3

Drag the tiles to the boxes to form correct pairs. Match each operation involving-example-1
User Surasin Tancharoen
by
6.6k points